The influence of operation time for hip hemiarthroplasty on complication rates and mortality in patients with femoral neck fracture: a retrospective data analysis: Letter to Editor - Raju Vaishya; Abhishek Vaish (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Ramadanov et al.‘s study highlights the importance of minimizing operative time in HHA for femoral neck fractures. Future prospective studies are needed to explore causality and refine strategies for achieving shorter, yet safe, procedures.